2015
DOI: 10.1016/j.molcata.2015.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous nanocrystalline TiO2 supported metal (Cu, Co, Ni, Pd, Zn, and Sn) catalysts: Effect of metal-support interactions on steam reforming of methanol

Abstract: a b s t r a c tMesoporous TiO 2 supported Cu, Co, Ni, Pd, Sn and Zn catalysts (M-TiO 2 ) were synthesized using facile onestep synthesis method and were characterized using BET, XRD, TGA-DSC, TEM, SEM-EDX, ICP-OES, and H 2 -TPR studies. The catalysts were further tested for steam reforming of methanol (SRM) to investigate their comparative catalytic performance. Depending on the nature of the metal component, the catalysts exhibited surface area, pore sizes, and TiO 2 crystallite sizes in the range of 99-309 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(69 citation statements)
references
References 71 publications
5
63
0
1
Order By: Relevance
“…Four peaks were detected for Ni 3 Mn 1 Ti 1 -LDO catalysts, which might be connected with the reduction of Mn 4 + À Mn 3 + À Mn 2 + , Ni 3 + À Ni 2 + À Ni 0 and Ti 4 + À Ti 3 + . [19,49] With the calcination temperature increasing, the location of reduction peaks shifted to higher temperature zones, which might be possibly related to the change of phase composition at higher calcination temperature, such as the generation of anatase TiO 2 , rutile TiO 2 and NiTiO 3 [50] in good accordance with XRD results. The phase composition of Ni 3 Mn 1 Ti 1 -LDO catalysts had a direct impact on interaction among manganese, nickel and titanium species, and further affected the reducibility.…”
Section: Characterization Of Ni 4-x Mn X Ti 1 -Ldhssupporting
confidence: 68%
“…Four peaks were detected for Ni 3 Mn 1 Ti 1 -LDO catalysts, which might be connected with the reduction of Mn 4 + À Mn 3 + À Mn 2 + , Ni 3 + À Ni 2 + À Ni 0 and Ti 4 + À Ti 3 + . [19,49] With the calcination temperature increasing, the location of reduction peaks shifted to higher temperature zones, which might be possibly related to the change of phase composition at higher calcination temperature, such as the generation of anatase TiO 2 , rutile TiO 2 and NiTiO 3 [50] in good accordance with XRD results. The phase composition of Ni 3 Mn 1 Ti 1 -LDO catalysts had a direct impact on interaction among manganese, nickel and titanium species, and further affected the reducibility.…”
Section: Characterization Of Ni 4-x Mn X Ti 1 -Ldhssupporting
confidence: 68%
“…The pore sizes of all the catalysts concentrated on the scope range from 5 to 15 nm. The shape of these isotherms showed a type IV isotherm (IUPAC classification) with a H4 hysteresis loop [31] located at 0.40 < P/P 0 < 1.0. All the features indicated that these catalysts belonged to typical mesoporous materials.…”
Section: Nitrogen Adsorption-desorption Resultsmentioning
confidence: 99%
“…However, three strong reduction peaks are seen at temperatures of 289, 329 and 577°C. The peak around 577°C is ascribed to the reduction of Ti 4+ ions [31]. The two peaks at lower temperature are believed to be a result of TiO 2 surface reduction.…”
Section: Physical and Structural Characterisationmentioning
confidence: 96%